PENERAPAN PSAK 71 PADA BANK BJB TAHUN 2021 - Dwi Urip Wardoyo; Bagas Rahmandita; Devy Tazkiyaturohmah; M Krisnadito Fauzan; Dede Pranatha (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
This study aims to determine the application of PSAK 71 to Bank BJB in 2021, as a regional-owned commercial bank with a core capital of Rp. 11.93 trillion and listed as the main board. This study uses qualitative methods, this study uses secondary data in the form of company financial statements for the 2020-2021 period. The conclusion that can be drawn is that the application of PSAK 71 accounting policies has taken effect on January 1, 2020, with the enactment of PSAK 71, bank BJB provides an allowance for impairment losses, although in implementation the percentage or number is different each year. In practice, there is an impairment loss which is reported as a deduction based on the carrying amount of financial assets in a number of groups of loans, then receivables which are recognized in the statement of profit or loss and other comprehensive income within the company